2020
DOI: 10.7554/elife.58593
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol interactions with voltage-gated sodium channels

Abstract: Voltage-gated sodium channels are targets for a range of pharmaceutical drugs developed for treatment of neurological diseases. Cannabidiol (CBD), the non-psychoactive compound isolated from cannabis plants, was recently approved for treatment of two types of epilepsy associated with sodium channel mutations. This study used high resolution X-ray crystallography to demonstrate the detailed nature of the interactions between CBD and the NavMs voltage-gated sodium channel, and electrophysiology to show the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 43 publications
7
47
0
3
Order By: Relevance
“…We found that GDF11 is relatively highly expressed in non-neurogenic regions like the thalamus, habenula, and cerebellum. Interestingly, we observed the highest density of Gdf11 expression in the habenula and our results align with a recent habenula focused single-cell RNA-sequencing paper which reported Gdf11 within the top 25% of highly expressed genes in the region [ 25 ]. The habenula contains primarily cholinergic neurons and has been shown to play an important role in cognition dependent executive functions and inhibitory control [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…We found that GDF11 is relatively highly expressed in non-neurogenic regions like the thalamus, habenula, and cerebellum. Interestingly, we observed the highest density of Gdf11 expression in the habenula and our results align with a recent habenula focused single-cell RNA-sequencing paper which reported Gdf11 within the top 25% of highly expressed genes in the region [ 25 ]. The habenula contains primarily cholinergic neurons and has been shown to play an important role in cognition dependent executive functions and inhibitory control [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…The CDOCKER program in the DS 2020 software (BIOVIA, Dassault Systems, Discovery Studio, 2020, San Diego, CA, USA) was employed to model the CBD docking to the human Na v 1.4 channel. The molecular mimicry screened for the CBD binding site potential in the human Na v 1.4 channel [ 39 ]. The X-ray diffraction structure of the human Na v 1.4 channel in complex with the β-subunit was downloaded from the Protein Data Bank (PDB ID: 6GAF; ) (19 October 2018) [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…An eukaryotic Nav channel comprises a single 2000-residue polypeptide chain, with four homologous domains arranged in a pseudotetrameric architecture, as verified by a handful of recent cryoEM structures reported in recent years (3)(4)(5)(6)(7)(8). In contrast, bacterial Nav channels are homotetramers with ~270 residues per subunit and have a simpler architecture with smaller intracellular and extracellular domains (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Despite their limited (~25%) sequence identity, bacterial Nav channels have been shown to share drug sensitivity and other functional properties with their eukaryotic counterparts, making them compelling model systems for structure/function studies (27).…”
Section: Introductionmentioning
confidence: 96%
“…Many efforts have been made to determine the structure of Nav channels in different functional states. Bacterial Nav channels have provided some insights, including structures of at least six subtypes (NavAb, NavMs, NavRh, NavCt, NaChBac and NavAe) in apparently distinct states (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Still, these structures were solved in a non-native environment (at cryogenic temperatures, solubilized by detergents) and often in the presence of mutations, so their functional assignments can be ambiguous.…”
Section: Introductionmentioning
confidence: 99%